Investigating The Effects Of Bite-Sized Learning Modules On Knowledge Acquisition And Retention In Jordan And Saudi Arabia (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this research is to investigate how well individuals are able to learn with the aid of these modules, how effectively individuals remember knowledge after using the modules, and how differently individuals in the two countries may learn and retain information. In order to conduct this quantitative research, participants were sought out from several institutions in Jordan and Saudi Arabia. The participants are separated into two groups: one group makes use of the bite-sized learning modules, while the other group continues to rely on more traditional approaches to learning. The acquisition of new knowledge may be evaluated using a pre-test and a post-test, whereas the retention of previously acquired knowledge can be evaluated using a series of tests taken in the future. The findings demonstrate that the people's knowledge in both Jordan and Saudi Arabia is significantly enhanced as a consequence of the bite-sized learning modules. On post-test measures, performance of participants who actively go through the courses is superior to that of the control group. People who utilize the bite-sized learning modules have substantially better knowledge retention, as can be evidenced by the excellent outcomes they get on future tests.